2015
DOI: 10.1016/j.ajpath.2015.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Rap1 GTPase Inhibits Tumor Necrosis Factor-α–Induced Choroidal Endothelial Migration via NADPH Oxidase– and NF-κB–Dependent Activation of Rac1

Abstract: Macrophage-derived tumor necrosis factor (TNF)-a has been found in choroidal neovascularization (CNV) surgically removed from patients with age-related macular degeneration. However, the role of TNF-a in CNV development remains unclear. In a murine laser-induced CNV model, compared with un-lasered controls, TNF-a mRNA was increased in retinal pigment epithelial and choroidal tissue, and TNF-a colocalized with lectin-stained migrating choroidal endothelial cells (CECs). Inhibition of TNF-a with a neutralizing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 35 publications
4
52
0
Order By: Relevance
“…C). Because Rac1‐biosensors rely on the intrinsic interaction of Rac1‐binding domains of Rac effectors with the active Rac, and this would interfere with the interaction of the active Rac1 moiety in the biosensor with JFC1, and therefore block the putative JFC1‐dependent localization of the Rac1 biosensor, we analyzed active Rac1 localization using a validated antibody that detects the endogenous active form of Rac1 (Rac1‐GTP) but not Rac1‐GDP . First, we confirmed the specificity of the antibody for endogenous Rac1‐GTP showing: (a) that the anti‐Rac1‐GTP antibody efficiently pulls down GTP‐loaded Rac1 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 65%
“…C). Because Rac1‐biosensors rely on the intrinsic interaction of Rac1‐binding domains of Rac effectors with the active Rac, and this would interfere with the interaction of the active Rac1 moiety in the biosensor with JFC1, and therefore block the putative JFC1‐dependent localization of the Rac1 biosensor, we analyzed active Rac1 localization using a validated antibody that detects the endogenous active form of Rac1 (Rac1‐GTP) but not Rac1‐GDP . First, we confirmed the specificity of the antibody for endogenous Rac1‐GTP showing: (a) that the anti‐Rac1‐GTP antibody efficiently pulls down GTP‐loaded Rac1 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 65%
“…17,21,22 In CNV, besides the RPE barrier, Rap1 may also regulate the barrier function of CECs to affect angiogenesis. 15,23 Therefore, an alternative interpretation to increased ZO-1 and occludin expression by 8CPT is that CECs have more stable tight junctions, and thus they are less likely to remodel and migrate ( Figure 5). This could yield an inhibition to CNV lesion.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that Rap1a de-escalates CNV development by interfering with ROSdependent signaling. 23 Similarly, in RPE inhibition of Rap1 by Rap1GAP increases ROS generation, whereas activation of Rap1 by 8CPT reduces ROS by interfering with NADPH oxidase assembly. 26 Our results in a rat laser-induced CNV model showed that reducing ROS generation by antioxidant apocynin treatment inhibited CNV formation in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 is a member of the Ras superfamily of Rho proteins, and it plays an essential role in many cellular processes, including mitogenesis, kinase cascade activation, transcriptional activation, DNA synthesis and cytoskeleton reorganization [37][38][39][40][41][42]. Rac1 overexpression has been found in various types of cancer, such as lung cancer, gastric cancer, pancreatic cancer, bladder cancer and breast cancer [43][44][45][46][47].…”
Section: R E T R a C T E Dmentioning
confidence: 99%